Trauma and psychosocial adversity in youth with autism spectrum disorder and intellectual disability - Palmer, Sarah J.; Dvir, Yael (Frontiers in Psychiatry, 2024)
Traumatic experiences contribute significantly to behavioral and mood dysregulation syndromes presenting for treatment to behavioral health settings. Individuals with Autism Spectrum Disorder (ASD), Intellectual Disability (ID) and developmental delay experience traumatic events more frequently than their typically developing peers. However, measures used to identify trauma related disorders and treatment thereof are based on typically developing individuals. Regardless of the baseline characteristics of individuals who experience trauma, trauma exposure is the result of multiple interdependent environmental, social, and familial characteristics. We used the "ecological systems analysis approach" to structure our review of the impact of trauma on those with ASD and ID. In addition, the COVID-19 pandemic which exposed the global population to a collective trauma, has also catalyzed investigations into the challenges faced by members of society most dependent on social services. Children with ASD and ID were among those vulnerable individuals, and the COVID-19 pandemic has allowed researchers to better understand the impact of a collective trauma on those individuals. It is imperative that we understand current research and recommendations for identifying and treating trauma-related disorders in individuals with developmental disorders to best inform clinical practice and directions for future research in this area.